A mini review of the pathogenesis of acute rheumatic fever and rheumatic heart disease - Zhuang, Shuting; Guo, Danchun; Yu, Dingle (Frontiers in Cellular and Infection Microbiology, 2025)
Acute rheumatic fever (ARF) is an autoimmune disease caused by group A streptococcal infection. Recurrent episodes of ARF can lead to rheumatic heart disease (RHD), which is the leading cause of cardiovascular mortality in children worldwide, especially in low- and middle-income countries. Investigations into the etiology of ARF and RHD constitute a crucial milestone in the advancement of both preventive measures and therapeutic interventions. The purpose of this mini review is to delineate the etiology and pathophysiological mechanisms underlying ARF and RHD. Selective searches were conducted in PubMed to retrieve literature published between 1968 and 2024, employing key terms such as “acute rheumatic fever”, “rheumatic heart disease”, “group A Streptococcus”, “streptococcal pharyngitis”, “pathogenesis”, and “pathophysiology”. The pathogenesis of infections caused by group A streptococci, and their effects on ARF and RHD, have been thoroughly examined. A central hypothesis is that autoimmune responses are triggered by molecular mimicry, but alternate pathogenic mechanisms are continuously being explored. There is an urgent need for high-quality research that can inform efforts aimed at decreasing the occurrence of ARF and halting the advancement of RHD, which requires researchers to understand its causes and to develop appropriate preventive and therapeutic programs.